Bed Rest, Exercise Countermeasure and Reconditioning Effects on the Human Resting Muscle Tone System - Schoenrock, Britt; Zander, Vanja; Dern, Sebastian; Limper, Ulrich; Mulder, Edwin; Veraksitš, Alar; Viir, Ragnar; Kramer, Andreas; Stokes, Maria J.; Salanova, Michele; Peipsi, Aleko; Blottner, Dieter (Frontiers in Physiology, 2018)
The human resting muscle tone (HRMT) system provides structural and functional support to skeletal muscle and associated myofascial structures (tendons, fascia) in normal life. Little information is available on changes to the HRMT in bed rest. A set of dynamic oscillation mechanosignals ([Hz], [N/m], log decrement, [ms]) collected and computed by a hand-held digital palpation device (MyotonPRO) were used to study changes in tone and in key biomechanical and viscoelastic properties in global and postural skeletal muscle tendons and fascia from a non-exercise control (CTR) and an exercise (JUMP) group performing reactive jumps on a customized sledge system during a 60 days head-down tilt bed rest (RSL Study 2015-2016). A set of baseline and differential natural oscillation signal patterns were identified as key determinants in resting muscle and myofascial structures from back, thigh, calf, patellar and Achilles tendon, and plantar fascia. The greatest changes were found in thigh and calf muscle and tendon, with little change in the shoulder muscles. Functional tests (one leg jumps, electromyography) showed only trends in relevant leg muscle groups. Increased anti-Collagen-I immunoreactivity found in CTR soleus biopsy cryosections was absent from JUMP. Results allow for a muscle health status definition after chronic disuse in bed rest without and with countermeasure, and following reconditioning. Findings improve our understanding of structural and functional responses of the HRMT to disuse and exercise, may help to guide treatment in various clinical settings (e.g. muscle tone disorders, neuro-rehabilitation), and promote monitoring of muscle health and training status in personalized sport and space medicine.